Estudo das citocinas e adipocinas de pacientes com lúpus eritematoso sistêmico atendidos no Serviço de Reumatologia do Hospital das Clínicas da UFMG - Fabiana de Miranda Moura (2015)
Introduction: Systemic lupus erythematosus (SLE) is an autoimmune disease whose etiology is poorly understood. This disease modified the functional response of lymphocytes T with increased Th1, Th2 and Th17 responses, reduced functional response of regulatory lymphocytes and subsequent modification of the profile of inflammatory and anti-inflammatory cytokines. Obesity can modify the inflammatory status of patients without autoimmune diseases. The adipose tissue of obese can produce high concentrations of adipokines (leptin and adiponectin) and also elevate serum levels of tumor necrosis factor alpha (TNF) and IL-6. The adipokine (leptin) can stimulate the production of these cytokines and consequently modify the inflammatory profile of obese individuals, however it is unknown whether this occurs in patients with SLE. In autoimmune diseases such as SLE, TNF participates in the inflammatory response, however the role of adipokines is not well defined. Objectives: Article 1 - To analyze the association of TNF and its receptors with clinical, laboratory and treatment-related manifestations of SLE; to study the association of adipokines with disease parameters in women with SLE; and to correlated the adipokines leptin, resistin and adiponectin and the TNF system. Article 2 - To analyze the cytokines profile of SLE patients and evaluate whether obesity interferes with the inflammatory status of these patients. Methods: Two cross-sectional studies were conducted at the Rheumatology Outpatient Clinic of the State University of Minas Gerais, in SLE women with older than 18 years of age. Data related to socio-demographic characteristics, clinical and laboratory manifestations and medication use were assessed. Article 1 A total of 136 women were assessed. Disease activity was measured by SLEDAI-2K modified index and irreversible cumulative damage by (SLICC-ACR/DI) index. Serum concentrations of TNF, soluble TNF receptors 1 (sTNFR1) and 2 (sTNFR2) and adipokines were analyzed using enzyme-linked immunosorbent assay (ELISA) kits. Article 2 One hundred eighty nine patients and 70 controls were included. Disease activity was measured by SLEDAI-2K index and irreversible cumulative damage by (SLICC-ACR/DI). Nutritional status was assessed by body mass index (BMI) and by bioimpedence. Serum concentrations of IL6, IL10, IL17, TNF, sTNFR1 and sTNFR2 were analyzed using high sensitivity cytometric bead array and adipokines (leptin and adiponectin) by enzyme-linked immunosorbent assay kits. Conclusion: Article 1: TNF, its receptors and adipokines were associated with arthritis and nephritis. The sTNFR1 correlated with global activity and the organic injury of lupus, suggesting that this could be used as a marker of disease activity. The resistin and leptin were associated with higher concentrations of TNF receptors. This correlation between the two systems (adipokines and TNF system) allows a better understanding of the role of adipokines in the inflammatory response in SLE patients. Article 2: This study showed higher concentrations of cytokines and adipokines in SLE patients than controls and showed that higher BMI was correlated with higher concentrations of IL6, IL17A and leptin. This finding suggests that the BMI found in the patients, interfere, regardless of disease activity in inflammatory profile of women with SLE.